Policy Reform and MSME Growth: Financial Analysis of 2023 KUR Disbursement Shift - Ridha, Muhammad Hafizh; Ashari, Hasan; Sancoko, Bambang; Damhuri, Taufik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in development, yet face persistent barriers to financing. To address this, the Indonesian government provides the People's Business Credit (KUR) program. In 2023, significant policy reforms were introduced concerning eligibility criteria and graduation interest rates, resulting in a decline in total disbursement. This study applies descriptive analysis and two-mean difference tests using data from 33 provinces (2022–2023) to evaluate the policy’s impact. The findings show that the revised KUR policy: (1) enhances financial inclusion, (2) supports debtor graduation, and (3) contributes to achieving the national MSME credit target. These results highlight the importance of policy reform in building a sustainable MSME financing ecosystem. The novelty of this study lies in integrating macro-level statistical evidence with field-based qualitative validation to uncover structural inefficiencies in government-backed microfinance. The findings offer policymakers actionable insights to refine MSME financing frameworks, particularly in enhancing credit accessibility and aligning distribution incentives.